2015
DOI: 10.1002/jmv.24353
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus increases the risk of kidney disease among HIV‐positive patients: Systematic review and meta‐analysis

Abstract: Kidney disease has become an important co-morbidity among human immunodeficiency virus-infected patients as they live longer in the era of highly effective antiretroviral therapy. It remains unclear how co-infection with hepatitis C virus impacts on the trajectory of kidney disease among HIV-infected patients. To evaluate the effect of co-infection with HCV on the risk of kidney disease in HIV-infected populations. We conducted a systematic review of the published medical literature to determine if hepatitis C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Studies performed in other subpopulations, including HCV/HIV‐coinfected patients and kidney transplant recipients, have provided further support for an impact of HCV infection on incident CKD. The presence of HCV coinfection in patients with HIV infection has been identified as a risk factor for CKD in several studies of different cohorts . A recent meta‐analysis incorporating studies that adjusted for potential confounders such as age, race, and history of injection drug use found a pooled aHR of 1.64 (95% CI, 1.28‐2.00) for the risk of incident CKD conferred by HCV coinfection .…”
Section: Association Of Hcv With Incident Ckdmentioning
confidence: 99%
“…Studies performed in other subpopulations, including HCV/HIV‐coinfected patients and kidney transplant recipients, have provided further support for an impact of HCV infection on incident CKD. The presence of HCV coinfection in patients with HIV infection has been identified as a risk factor for CKD in several studies of different cohorts . A recent meta‐analysis incorporating studies that adjusted for potential confounders such as age, race, and history of injection drug use found a pooled aHR of 1.64 (95% CI, 1.28‐2.00) for the risk of incident CKD conferred by HCV coinfection .…”
Section: Association Of Hcv With Incident Ckdmentioning
confidence: 99%
“…Recent meta-analyses of general-population [3] and HIV-positive [4] cohorts reported 45% and 64% increased risks of developing CKD (stage 3 or higher), respectively, in HCV seropositive versus seronegative individuals.…”
mentioning
confidence: 99%
“…In particular, emergency department visits related to kidney disease were much more common among coinfected patients (37%) than among those with HIV infection alone (10%). 62 Another meta-analysis of observational studies 63 reported a relationship between positive anti-HCV serologic status and an increased risk of reduced GFR among HIV-infected individuals, with an adjusted HR of 1.64 (95% CI: 1.28-2.0), compared with those having HIV infection alone.…”
Section: 41mentioning
confidence: 99%
“…281 A large meta-analysis of 107,356 patients 7 reported that anti-HCV-positive serology was an independent risk factor for proteinuria in the adult general population (adjusted OR: 1.51 [95% CI: 1.19-1.89)]. 65,66,[282][283][284][285] Another pooled analysis 63 demonstrated that anti-HCVpositive serology was an independent risk factor for proteinuria among HIV-infected patients with an adjusted effect estimate of 1.23 (95% CI: 1.18-1.28). [286][287][288][289][290][291] 5.1: We recommend that a kidney biopsy be performed in HCV-infected patients with clinical evidence of glomerular disease (Not Graded).…”
Section: Chapter 5: Diagnosis and Management Of Kidney Diseases Assocmentioning
confidence: 99%